Synthesis, crystal structure, cytotoxicity and action mechanism of a Rh(iii) complex with 8-hydroxy-2-methylquinoline as a ligand12. Issue 1 (15th November 2016) - Zhang, Yun-Liang; Qin, Qi-Pin; Cao, Qian-qian; Han, Hong-Hua; Liu, Zhu-Ling; Liu, Yan-Cheng; Liang, Hong; Chen, Zhen-Feng
Abstract : 1 exerted its cytotoxic activity mainly via disruption of mitochondrial function, and significantly caused S phase arrest. Abstract : A rhodium(iii ) complex, [Rh(MQ)(DMSO)2 Cl2 ] (1 ), with 8-hydroxy-2-methylquinoline as the ligand was synthesized and characterized. Complex1 exhibited cytotoxicity against BEL-7404, Hep-G2, NCI-H460, T-24, and A549 cell lines with IC50 values in the micromolar range (6.52–17.86 μM). Various experiments on the Hep-G2 cells showed that complex1 caused cell cycle arrest at the S phase, downregulation of cdc25 A, cyclin A, cyclin B and CDK2, and upregulation of p21, p27 and p53. Furthermore, cytotoxicity mechanism studies suggested that complex1 -induced apoptosis was achieved via disruption of the mitochondrial function, which led to a significant loss of the mitochondrial membrane potential, an increase in the cellular levels of reactive oxygen species, cytochrome c, and apaf-1, and a fluctuation of the intracellular Ca 2+ concentration. Taken altogether, complex1 can trigger cancer cell death by inducing apoptosis through a mitochondrial dysfunction pathway.